Risk indicators of edentulism, partial tooth loss and prosthetic status among black and white middle-aged and older adults - Dolan TA, Gilbert GH, Duncan RP, Foerster U. (Blackwell Synergy, 2001)
To describe the prevalence and risk indicators of edentulism; to describe the frequencies of wearing removable dentures; to describe the prevalence and risk indicators of fixed prosthetic restorations; to test the hypothesis that fixed prosthetic restorations are most likely to have been placed in persons at lower risk for dental and periodontal diseases, and to test the hypothesis that, with dental disease, dental behaviors, dental attitudes and ability to afford crowns taken into account, blacks are less likely than whites to have received crowns.